2020
DOI: 10.4103/jehp.jehp_679_19
|View full text |Cite
|
Sign up to set email alerts
|

Maternal early pregnancy body mass index and pregnancy outcomes among nulliparous women registered in tertiary care hospital and urban slum hospital of a metropolitan city

Abstract: BACKGROUND: Underweight is still prevalent in developing countries like India. Prepregnancy body mass index (BMI) is used as the standard against which the measurements are made in pregnancy. AIM: To study the association between early pregnancy BMI and feto-maternal outcome among nulliparous women METHODOLOGY: This is a prospective observational study, with a sample size of 294. The antenatal patients were categorized into four categories of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Data from human epidemiologic studies suggest that maternal undernutrition impairs placental formation, leading to a reduction in placental size, alterations in histomorphology, and reduction of blood flow, which can diminish nutrient delivery to the fetus [10]. A low early pregnancy BMI has been associated with low birth weight (LBW) and preterm birth [3]. In addition to fetal growth restriction, maternal undernutrition has been associated with LBW and preterm delivery, plus the short-and long-term complications associated with these outcomes, and with maternal complications, such as life-threatening hemorrhage [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from human epidemiologic studies suggest that maternal undernutrition impairs placental formation, leading to a reduction in placental size, alterations in histomorphology, and reduction of blood flow, which can diminish nutrient delivery to the fetus [10]. A low early pregnancy BMI has been associated with low birth weight (LBW) and preterm birth [3]. In addition to fetal growth restriction, maternal undernutrition has been associated with LBW and preterm delivery, plus the short-and long-term complications associated with these outcomes, and with maternal complications, such as life-threatening hemorrhage [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…During the past few years, a secular trend toward increased birth weight and macrosomia related to greater maternal weight has been observed [ 2 ]. Early pregnancy overweight and obesity have been associated with adverse maternal outcomes [ 3 ]. Macrosomia increases the risk of cesarean delivery, shoulder dystocia, and subsequent childhood obesity [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gestational weight gain (GWG) is a unique and complex biological phenomenon to support normal fetal growth and development [ 1 ]. This phenomenon is caused by changes in the uterus and its contents such as placenta, amniotic fluid, fetus, as well as metabolic changes in the mother's body, including the accumulation of fluid and fat [ 2 ]. The U.S. Institute of Medicine (IOM) has recommended guidelines to help physicians in monitoring adequate GWG [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown that maternal and fetal fat mass gain are positively correlated with initial body mass index (BMI) levels 6 . Prepregnancy BMI is the most accurate measure of maternal obesity but, if booking is done in the first trimester, first‐trimester BMI may then be an alternative measure of maternal obesity because weight gain is usually at its lowest in the first trimester (0.5–2 kg) 7 . Reports show that in Nigeria, most women do not book in the first trimester 8 .…”
Section: Introductionmentioning
confidence: 99%